The Disparity in Greenspace Quality Between Low and High SES Settings: A Case Study in Victoria. Issue 5 (1st November 2022) - Ghanem, Ali; Edirisinghe, Ruwini
Abstract: The presence of greenspace, its profound impact and association with physical and mental health, biodiversity, and aesthetical pleasure has been delineated abundantly. Contrarily, there is a concerning disparity in the accessibility and proximity between affluent and deprived areas in urbanised localities. Existing literature prioritised distribution and proximity domains when assessing inequitable greenspace and consequently has catalysed a research gap in greenspace quality domains. This paper endeavours to fill this gap through a case study in Melbourne, Australia using a quantitative method to extract findings and policy analysis to generate recommendations. Socioeconomic data from deprivation indexes systematically defined low and high SES (socioeconomic status). A GIS (Geographical Information System) observation of greenspaces scored spaces according to a scoring criterion contingent on safety/security, environmental elements, accessibility, maintenance/cleanliness, facilities/amenities, and aesthetic facets. Statistics were then synthesised to produce a Cohen effect score highlighting disparities in each facet between the two contrasting SES groups. Findings affirmed an existent disparity between the high and low SES spaces and contributed to existing strands of literature surrounding unjust quality distribution. Ultimately, findings will serve as invaluable evidence regarding policy implications, current opportunities under the 'Plan Melbourne' policy, and the need to facilitate intervention in those underprivileged settings.